Exercise and Atrial Fibrillation: Some Good News and Some Bad News: - Sepehri Shamloo, Alireza; Arya, Arash; Dagres, Nikolas; Hindricks, Gerhard (Galen Medical Journal, 2018)
Atrial fibrillation (AF) is considered as the most common sustained arrhythmia in adults, whose incidence rate is on the rise due to the increase in the mean age of the global population. In recent years, many efforts have been made to identify effective factors in the incidence of AF to prevent them and thereby reduce the consequences of AF. Physical activity is one of the topics that attracted much attention in the last two decades. According to some findings, extreme and prolonged exercise itself can be considered as a risk factor for the onset of AF; however, other studies have shown that exercise can be regarded a protective factor against AF in the general population. The present study reviews the findings of studies on the relationship between AF and exercise and discusses possible mechanisms for this relationship. Additionally, we present some recommendations for researchers and physicians about exercise management in association with AF prevention.Â [GMJ.2018;7:e1401]Â 